Reproducción del pez Brotula clarkae (Pisces: Ophidiidae) en el Pacífico colombiano - Acevedo, Jenny (2007)
We studied the reproductive ecology of the fish Brotula clarkae based on 754 individuals obtained from the industrial and artisanal fisheries in the Colombian Pacific (March 1994 to December 1996). Histological sections (paraplast embedding and Harris’s hematoxylin-eosin stain) were made from 151 females (26-100 cm total length). Additionally, mean diameter and particular features are described for oocyte phases and ovarian development stages. The mean size at initial sexual maturity of females was determined with two methods (graphic and statistic) in 61.3 cm and 62.3 cm respectively. The general sex ratio was 1:1.There are several spawn pulses between May and October. The mean fecundity by spawn pulse was 1 005 657 eggs. We recommend a fishing ban during the reproduction period and a minimal catch size above 62.3 cm.